A study of level of understanding of the customer in the Ikhtiari Group Life Insurance / Kamariah Abu - Abu, Kamariah (Faculty of Business and Management, 2003)
This study evaluates the level of understanding of the customer with MCIS IKHTIARI scheme. The overall result of this study indicated that most of the insured are not understood with the scheme explained to them. This problem happened because of lack of communication between agent (From Fazil Agency) and insured. The terms that are used in the policy and proposal are not clear and detail as to give a better understanding that means, the agent should improve a communication programs that can increase level of understanding to insured.